2021
DOI: 10.3390/cells10112817
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Induced Blocking Factor Reduces Hypertension and Placental Mitochondrial Dysfunction in Response to sFlt-1 during Pregnancy

Abstract: Preeclampsia (PE) is characterized by new onset hypertension in association with placental ischemia, reduced fetal weight, elevated soluble fms-like tyrosine kinase-1 (sFlt-1), and placental mitochondrial (mt) dysfunction and oxidative stress (ROS). Progesterone induced blocking factor (PIBF) is a product of progesterone signaling that blocks inflammatory processes and we have previously shown PIBF to lower mean arterial blood pressure (MAP) and sFlt-1 in a rat model of PE. Infusion of sFlt-1 causes hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Progesterone protects vasodilation by regulating levels of cytokines (such as interleukin-6), which can block inflammation. In two clinical trial studies, negative associations of progesterone with DBP and MAP were found, which is consistent with our results [26][27][28]. In accordance with our findings, the results of the above studies have also shown that progesterone is not associated with SBP in men [29,30].…”
Section: Discussionsupporting
confidence: 93%
“…Progesterone protects vasodilation by regulating levels of cytokines (such as interleukin-6), which can block inflammation. In two clinical trial studies, negative associations of progesterone with DBP and MAP were found, which is consistent with our results [26][27][28]. In accordance with our findings, the results of the above studies have also shown that progesterone is not associated with SBP in men [29,30].…”
Section: Discussionsupporting
confidence: 93%
“…In an arginine vasopressin model of PreE, male offspring of PreE dams exhibited increased social behavior in the three-chamber social preference task relative to control offspring, without there being a significant difference in distance travelled between the groups [ 53 ]. Our study is not without limitations, firstly even though it has previously been demonstrated that these animal models have hypertension and inflammation during pregnancy we did not directly evaluate that in the dams that birthed the offspring used in the current study [ 20 , 54 ]. We also did not measure the immune profile of these offspring as immune activation during pregnancy can be correlated with neurodevelopmental outcome of offspring [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Teran et al showed that women with PE have already-established alterations in the levels of mitochondria targeting antioxidant coenzyme (CoQ10) in the plasma and in the placenta, as compared to normal pregnant women ( Teran et al, 2001 ; Smith et al, 2021 ). Improved mitochondrial function and ROS are associated with improved blood pressure in sFLT-1-induced hypertensive pregnant rats ( Deer et al, 2021 ). CALCA is shown to protect myocardial cells against oxidative stress through a mitochondrial-dependent pathway, suggesting the involvement of mitochondria in the vascular action of CALCA ( Tullio et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%